Thiopurines prevented surgical recurrence in patients with Crohn's disease after intestinal resection: Strategy based on risk stratification. Issue 3 (22nd February 2018) - Guo, Jing; Chen, Bai‐li; Chen, Zhi‐hui; Luo, Xia‐peng; Qiu, Yun; Zhang, Sheng‐hong; Feng, Rui; He, Yao; Zeng, Zhi‐rong; Song, Xin‐ming; Ben‐Horin, Shomron; Mao, Ren; et al.
Abstract: Background and Aim: Thiopurines (TPs) are effective in reducing clinical and endoscopic recurrence in postoperative patients with Crohn's disease (CD). However, whether TPs could prevent surgical recurrence (SR) remains unknown. We aimed to explore whether TPs could prevent SR and identify risk factors associated with SR. Methods: This was a retrospective cohort study of 246 postoperative patients with CD. Cox proportional hazard model was used to identify risk factors for SR. Patients were stratified according to the presence of risk factors. Results: A total of 50 (20.3%) patients suffered SR after a mean follow up of 54.3±46.4 months. Multivariable analysis showed independent risk factors for SR were penetrating disease behavior (HR 8.628; 95% CI 1.573–47.341; P = 0.01), ileocolonic disease location (HR 2.597; 95% CI 1.047–6.445; P = 0.04) and isolated upper gastrointestinal disease (UGID) location (HR 5.082; 95% CI 1.496–17.267; P = 0.009). However, use of TPs after surgery significantly reduced the risk of SR (HR 0.120; 95% CI 0.063–0.231; P < 0.001). When stratifying patients according to risk factors, there was no statistical difference of SR between patients treated or not by TPs ( P = 0.08) in low‐risk group ( n = 46). However, in high risk group ( n = 200), patients with TPs use had a lower risk of SR than those without TPs (HR 0.093; 95% CI 0.048–0.178; P < 0.001). Conclusions: Penetrating disease behavior and ileocolonic/isolated (UGID) location were associated with SR in CD patients. TPs use was beneficial in decreasing risk for SR in CD patients at high risk.